Exploring the relationship between psoriasis and vitamin D - Kiełczewska, Aleksandra; Szcześniak, Grzegorz; Kiełczewska, Anna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Psoriasis is a chronic, inflammatory skin condition that affects millions of individuals worldwide. Recent research has suggested a potential link between psoriasis and vitamin D deficiency. This review paper aims to examine the existing literature on the relationship between psoriasis and vitamin D, exploring the potential role of vitamin D in the pathogenesis and management of this debilitating skin disorder. Materials and method: An extensive examination of articles published in scientific journals was carried out through online research platforms PubMed and Google Scholar. We searched articles by entering keywords in appropriate configuration: “psoriasis”, “vitamin D”, “obesity”. Description of the state of knowledge: Emerging research has identified a connection between vitamin D and the development of various skin conditions, including psoriasis. Consistent findings have shown a significant association between low vitamin D levels and the presence of psoriasis. Furthermore, due to vitamin D’s influence on the proliferation and maturation of keratinocytes, it has become an important local treatment option for managing psoriasis. Summary: Although there is no clear consensus on whether sufficient dietary vitamin D or oral vitamin D supplements effectively treat psoriasis, the available evidence is still inconclusive. However, healthcare providers like nutritionists should consider recommending general vitamin D supplementation for populations at high risk of vitamin D deficiency, such as those with psoriasis or obesity.